2010
DOI: 10.1038/npp.2010.203
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Interactive Effects of Glycine and D-Cycloserine in Men: Further Evidence for Enhanced NMDA Receptor Function Associated with Human Alcohol Dependence

Abstract: Reduced responses to N-methyl-D-aspartate (NMDA) glutamate receptor antagonists in alcohol-dependent animals and humans provided evidence that chronic alcohol consumption increased NMDA receptor function. To further probe alterations in NMDA glutamate receptor function associated with human alcohol dependence, this study examined the interactive effects of agents acting at the glycine(B) coagonist site of the NMDA receptor. In doing so, it tested the hypothesis that raising brain glycine concentrations would a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
0
20
0
2
Order By: Relevance
“…Behavioral measures in human alcoholics reveal reduced sensitivity to the perceptual and cognitive disrupting effects of the noncompetitive NMDA antagonist ketamine (Krystal et al, 2003). Human alcoholics also reported less alcohollike effect of the partial glycine agonist D-cycloserine as compared to control subjects, suggesting alterations in glutamatergic signaling in alcohol-dependent individuals (Krystal et al, 2011). Studies of the effects of glutamatergic drugs on drinking in humans are more limited than those in animals due in part to the significant side effects that these agents have.…”
Section: Ionotropic Glurs-human Studiesmentioning
confidence: 97%
“…Behavioral measures in human alcoholics reveal reduced sensitivity to the perceptual and cognitive disrupting effects of the noncompetitive NMDA antagonist ketamine (Krystal et al, 2003). Human alcoholics also reported less alcohollike effect of the partial glycine agonist D-cycloserine as compared to control subjects, suggesting alterations in glutamatergic signaling in alcohol-dependent individuals (Krystal et al, 2011). Studies of the effects of glutamatergic drugs on drinking in humans are more limited than those in animals due in part to the significant side effects that these agents have.…”
Section: Ionotropic Glurs-human Studiesmentioning
confidence: 97%
“…DCS has been shown to increase the channel open time at NMDARs containing the NR2C subunit with ~200% efficacy compared to glycine, whereas at NMDARs containing NR2A or 2B subunits, DCS has approximately 50% efficacy compared to glycine. 72 Thus, while DCS is an agonist at NMDARs with NR2C subunits regardless of dose, at NMDARs with NR2B and NR2A subunits, DCS may act as an agonist at low doses (eg, 50-250 mg) by stimulating unoccupied glycine sites, but as an antagonist at high doses (eg 1000 mg) 73 by displacing endogenous glycine. We chose a low DCS dose that was likely to act as an agonist across NMDAR subtypes and we previously found that 100 mg DCS enhanced plasticity in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Глицин (Gly) выполняет в организме целый ряд жизненно важных функций [1][2][3][4][5][6][7][8][9]. Он входит в состав многих белков и биологически активных соединений, из него синтезируются порфириновые кольца гема и пуриновые основания [10].…”
Section: Introductionunclassified
“…Рецепторы к Gly, локализованные во многих участках головного и спинного мозга, оказывают тормозное воздействие на нейроны, уменьшая выделение возбуждающих аминокислот [1][2][3]. В то же время глицин выступает в роли коагониста рецептора g-аминобутирата (GABA-R) и глутаматного рецептора NMDA-R [4][5][6][7][8].…”
Section: Introductionunclassified